Use of Social Media, Satisfaction with Body Image, and the Risk of Manifesting Eating Disorders - Ángeles Arjona; Montserrat Monserrat; Juan Carlos Checa (Social Sciences, 2024)
Eating disorders in adolescents are an increasingly important issue nowadays. Although they have been shown to be a pathology with multifactorial causes, the objective of our study is to determine the degree of influence that body dissatisfaction and the use of social media (time and type) might have on the risk of manifesting eating disorders. To perform this, the Sick Control One Fat Food scale was used as part of a randomized survey carried out among 12 schools in Almería (Spain). The sample consisted of 605 students in Compulsory Secondary Education between the ages of 12 and 17 years (M = 14.27; SD = 1.44), 48.42% female and 51.52% male. Cross-tabulation tables were constructed to observe the relationship of sex and age with the risk of manifesting EDs, and, subsequently, a two-factor ANOVA was performed using the risk of suffering from an eating disorder as a dependent variable. The results show that 29.3% of the respondents express an elevated risk of suffering from an eating disorder. There are no significant differences regarding sex, but there are differences regarding age. It was also observed that dissatisfaction with body image is a significant risk factor, but not the time that young people spend on social media. Furthermore, the type of content displayed on social media has a significant influence, both independently and together with body dissatisfaction. The main conclusion highlighted in this study relates to the importance of self-perceived body image (satisfaction and dissatisfaction) and its relationship with the type of content seen on social media. For this reason, it is essential to work on self-esteem at an early age as well as learn to value others and oneself beyond just the physical.